The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s41121-018-0016-7
|View full text |Cite
|
Sign up to set email alerts
|

The preservation of teeth with root-originated fractures

Abstract: Traditionally, when a root-originated fracture (ROF) was diagnosed in an endodontically treated tooth, the tooth was scheduled for extraction. However, modern endodontics offers new treatment options to manage and maintain certain ROF teeth. The decision of whether to extract a ROF tooth and substitute it with a dental implant, or to implement a more conservative management approach by attempting an additional endodontic treatment aimed to preserve the natural tooth, is complicated and multifactorial. The mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
0
7
0
Order By: Relevance
“…The high positive interaction between resection and preparation suggests that a high resection is indicated for a high preparation . This result can be explained by the fact that a high preparation level induces very thin dentin walls prone to fracture, but this would have been attenuated by a higher level of resection [ 25 ]. Considering all coefficients of the equation, the DOE suggested that nearly half of the biomechanical impact is missed without considering interactions between factors, which is of great importance because these interactions should be present in all situations encountered in EMS.…”
Section: Discussionmentioning
confidence: 99%
“…The high positive interaction between resection and preparation suggests that a high resection is indicated for a high preparation . This result can be explained by the fact that a high preparation level induces very thin dentin walls prone to fracture, but this would have been attenuated by a higher level of resection [ 25 ]. Considering all coefficients of the equation, the DOE suggested that nearly half of the biomechanical impact is missed without considering interactions between factors, which is of great importance because these interactions should be present in all situations encountered in EMS.…”
Section: Discussionmentioning
confidence: 99%
“…Intentional replantation has also been used as a method that allows extra-oral bonding of teeth with vertical root fractures (Hayashi et al, 2002(Hayashi et al, , 2004Nizam et al, 2016;Okaguchi et al, 2018;Rosen et al, 2018;Sugaya et al, 2016). It has also been used as a treatment option to treat teeth considered as having a periodontally poot prognosis (Hou et al, 2016;Saida et al, 2018;Solakoglu & Filippi, 2017).…”
Section: Intentional Replantationmentioning
confidence: 99%
“…Teeth with vertical root fractures are usually deemed nontreatable. However, in the rare cases in which maintaining a tooth with vertical root fracture seems crucial due to no alternative treatment options, intentional replantation with extraoral fragment bonding as part of the procedure has been proposed (Rosen et al 2018). A special adhesive resin containing 4‐methacryloxyethyl trimellitate anhydride/methyl methacrylate‐tri‐n‐butyl borane (4‐META/MMA‐TBB) was used to bond the fragments (Hayashi et al 2002, 2004, Nizam et al 2016, Sugaya et al 2016).…”
Section: Clinical Proceduresmentioning
confidence: 99%
“…More recent reports have used intentional replantation to enable extraoral bonding of teeth with vertical root fractures (Hayashi et al 2002, 2004, Nizam et al 2016, Sugaya et al 2016, Okaguchi et al 2018, Rosen et al 2018) or to treat teeth considered as having a periodontally hopeless prognosis (Hou et al 2016, Solakoglu & Filippi 2017, Saida et al 2018).…”
Section: Introductionmentioning
confidence: 99%